(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The object of this report is study the influence of gamma quanta on some parameters of the unijunction transistors to synthesize radioisotope equipment.